2005
DOI: 10.1073/pnas.0405667102
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a free-living chlorophyll d -producing cyanobacterium with a hybrid proteobacterial/cyanobacterial small-subunit rRNA gene

Abstract: Chlorophyll d-producing cyanobacteria are a recently described group of phototrophic bacteria that is a major focus of photosynthesis research, previously known only from marine environments in symbiosis with eukaryotes. We have discovered a free-living member of this group from a eutrophic hypersaline lake. Phylogenetic analyses indicated these strains are closely related to each other but not to prochlorophyte cyanobacteria that also use an alternative form of chlorophyll as the major light-harvesting pigmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
129
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(148 citation statements)
references
References 39 publications
7
129
0
Order By: Relevance
“…Even if one of these scenarios did apply to strain ATCC 16529, it ought to be followed by further recombination of divergent gene fragments between intragenomic operons. Specifically, recombination is obviously necessary to form mosaic genes in the first scenario, but also in the second to explain the observed highly segmental nature of 18S rRNA genes, as loci for recombination via LGT between organisms are restricted in SSU rRNA genes (Wang & Zhang, 2000;Gogarten et al, 2002;Miller et al, 2005). In any case, it is plausible that a mobile genetic element-like mechanism (which works in a single genome) might play a role in the formation of the complex mosaic structure observed here.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Even if one of these scenarios did apply to strain ATCC 16529, it ought to be followed by further recombination of divergent gene fragments between intragenomic operons. Specifically, recombination is obviously necessary to form mosaic genes in the first scenario, but also in the second to explain the observed highly segmental nature of 18S rRNA genes, as loci for recombination via LGT between organisms are restricted in SSU rRNA genes (Wang & Zhang, 2000;Gogarten et al, 2002;Miller et al, 2005). In any case, it is plausible that a mobile genetic element-like mechanism (which works in a single genome) might play a role in the formation of the complex mosaic structure observed here.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, it is not clear whether or not LGT is responsible for the occurrence of identical base pairs in those hairpins of SSU rRNA in different actinomycetes. In the second case, two strains of a chlorophyll d-producing cyanobacterium have been found to have gained a single hairpin helix in variable region V1 of the SSU rRNA from a b-proteobacterium (Miller et al, 2005). In the third case, comparative sequence analysis of six rRNA operons of the actinomycete Thermomonospora chromagena has revealed that the SSU rRNA gene of one operon (rrnB) contains two or three regions that were likely derived from a different species, Thermobispora bispora, whereas sequences of the corresponding genes from the remaining five operons in T. chromagena (rrnA, rrnC, rrnD, rrnE and rrnF) are almost identical with each other and lack evidence for interspecific recombination (Yap et al, 1999;Gogarten et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations